Photoperiod-Induced Increases in Bone Mineral Apposition Rate in Siberian Hamsters and the Involvement of Seasonal Leptin Changes - Kokolski, Marie; Ebling, Francis J.; Henstock, James R.; Anderson, Susan I. (Frontiers in Endocrinology, 2017)
The adipokine leptin regulates energy balance, appetite, and reproductive maturation. Leptin also acts on bone growth and remodelling, but both osteogenic and anti-osteogenic effects have been reported depending on experimental conditions. Siberian hamsters (Phodopus sungorus) have natural variation in circulating leptin concentrations, where serum leptin is significantly decreased during the short day-induced winter state (SD). In summer long day photoperiods (LD), appetite and body adiposity increase, with associated central leptin insensitivity. This natural change in leptin secretion was exploited to investigate leptin’s effect on bone growth. Hamsters were injected with calcium-chelating fluorescent dyes to measure bone mineral apposition rate (MAR). Measurements were initially obtained from 5-week and 6-month-old animals maintained in low leptin (SD) or high leptin (LD) states. A further study investigated effects of chronic administration of recombinant mouse leptin to hamsters housed in SD and LD conditions; growth plate thickness and bone density were also assessed. As expected, a reduction in body mass was seen in hamsters exposed to SD, confirming the phenotype change in all studies. Serum leptin concentrations were significantly reduced in SD animals in all studies. MAR was reproducibly and significantly increased in the femurs of SD animals in all studies. Vitamin D and Growth Plate thickness were significantly increased in SD animals at 6 months. No effect on bone density was observed in any study. Taken together these data suggest bone growth is associated with the low leptin, winter, lean state. In leptin-treated animals there was a significant interaction effect of leptin and photoperiod. In comparison to their vehicle counterparts, SD animals had decreased and LD animals had increased mineral apposition rate, which was not apparent prior to leptin administration. In conclusion, increased MAR was associated with low serum leptin levels in early life and sustained over 6 months, implying leptin has a negative effect on bone growth in this model. The unexpected finding that MAR increased after peripheral leptin administration in LD suggests leptin exerts different effects on bone growth dependent on initial leptin status. This adds further weight to the hypothesis that leptin-treated LD animals display central leptin resistance.